函数\(z = \ln \left( {3x + {y^4}} \right)\)的全微分为
A: \(dz = { { 3 + {y^4}} \over {3x + {y^4}}}dx + { { 3x + 4{y^3}} \over {3x + {y^4}}}dy\)
B: \(dz = {3 \over {3x + {y^4}}}dx + { { 4{y^3}} \over {3x + {y^4}}}dy\)
C: \(dz = {3 \over {3x + {y^4}}}dy + { { 4{y^3}} \over {3x + {y^4}}}dx\)
D: \(dz = {3 \over {3x + {y^4}}}dx - { { 4{y^3}} \over {3x + {y^4}}}dy\)
A: \(dz = { { 3 + {y^4}} \over {3x + {y^4}}}dx + { { 3x + 4{y^3}} \over {3x + {y^4}}}dy\)
B: \(dz = {3 \over {3x + {y^4}}}dx + { { 4{y^3}} \over {3x + {y^4}}}dy\)
C: \(dz = {3 \over {3x + {y^4}}}dy + { { 4{y^3}} \over {3x + {y^4}}}dx\)
D: \(dz = {3 \over {3x + {y^4}}}dx - { { 4{y^3}} \over {3x + {y^4}}}dy\)
举一反三
- 如下C程序的输出是什么?#include [stdio.h]void Func1 (int x, int y);void Func2 (int *x, int *y); int main() { int x = 3; int y = 4;Func1 (x, y); printf ("x = %d, y = %d\n", x, y);Func2(&x, &y); printf ("x = %d, y = %d\n", x, y);} void Func1 (int x, int y) { x = x + y; y = x - y; x = x - y; printf ("x = %d, y = %d\n", x, y);} void Func2 (int *x, int *y) { *x = *x + *y; *y = *x - *y; *x = *x - *y;;} A: x = 3, y = 4x = 3, y = 4x = 3, y = 4 B: x = 4, y = 3x = 4, y = 3x = 4, y = 3 C: x = 3, y = 4x = 3, y = 4x = 4, y = 3 D: x = 4, y = 3x = 3, y = 4x = 4, y = 3
- 函数\(y = \cos (4 - 3x)\)的导数为( ). A: \( - 3\sin \left( {4 - 3x} \right)\) B: \(3\sin \left( {4 - 3x} \right)\) C: \(3\sin \left( {4 + 3x} \right)\) D: \( - 3\sin \left( {4 + 3x} \right)\)
- 已知直线的一般方程\( \left\{ {\matrix{ {x - 2y - z + 4 = 0} \cr {5x + y - 2z + 8 = 0} \cr } } \right. \), 则其点向式方程为( ) A: \( { { x - 2} \over 2} = {y \over { - 3}} = { { z - 4} \over {11}} \) B: \( {x \over 5} = {y \over { - 3}} = { { z - 4} \over {11}} \) C: \( { { x - 2} \over 5} = { { y + 1} \over { - 3}} = { { z - 4} \over {11}} \) D: \( { { x - 2} \over 2} = { { y + 1} \over { - 3}} = { { z - 4} \over {11}} \)
- 下列语句正确的是( ) A: If x<3*y And x>y Then y=3x B: If x<3*y And x>y Then y=x^3 C: If x<3*y : x>y Then y=x^3 D: If x<3*y And x>y Then y=x**3
- 设\(D = \left\{ {(x,y)\left| { { x^2} + {y^2} \le 4,x \ge 0,y \ge 0} \right.} \right\}\),则\(\int\!\!\!\int\limits_D {(x + y)} d\sigma = \) A: \(0\) B: \( { { 8} \over 3}\) C: \( { { 16} \over 3}\) D: \( { { 32} \over 3}\)